Exploring the Assessment of Inflammation and Erosion in the Metatarsalphalangeal Joints of patients with Early Rheumatoid Arthritis Using Clinical Examination, Ultrasonography and Magnetic Resonance Imaging - Zou, Hanyan (My University, 2018)
Introduction Disease monitoring in rheumatoid arthritis (RA) can be improved by incorporating imaging technologies. Clinical examination fails to detect subclinical inflammation in half of metatarsophalangeal joints (MTPJs), but the effectiveness of using ultrasonography (US) in MTPJs is unclear. We aimed to evaluate US assessment of disease activity in the MTPJs using MRI as the reference standard, in comparison to clinical examination. Methods Patients newly diagnosed with RA (ACR criteria) were recruited and assessed at baseline, 6 weeks, 3 months, 6 months, and 12 months. A rheumatologist assessed the MTPJs 2-5 bilaterally for swelling and tenderness (presence=1), and for erosion (presence=1), synovial thickening, and power Doppler (PD) by US. Synovial thickening and PD were graded semi-quantitatively (grade 0-3). The most clinically symptomatic foot was scanned using extremity MRI (1.0T) at the baseline and 12-month visits. MTPJs 2-5 were graded semi-quantitatively for synovitis, bone marrow edema (BME) (grade 0-3), and erosions (grade 0-10). Results Forty-one patients were recruited (mean (SD) age=51.9 (10.3) years, 81% female). Kappa agreement was moderate between PD and grade ≥2 synovitis (k=0.46) and BME (k=0.47), but poor agreement was found for clinical examination and synovial thickening. US was able to visualize subclinical inflammation in 41% of non-swollen joints. After 12 months, the average total score for synovial thickening, PD, and BME all significantly decreased, but not swollen or tender joint counts. US visualized few erosions (n=8) compared to MRI (n=101) in the most symptomatic foot. MRI observed erosion repairs in patients treated with DMARDs, and repairs appeared to be preferential for MTPJs that had low inflammation seen by US. Conclusion US appears to better visualize MTPJ inflammation than swollen and tender joint counts, and may be used in combination with clinical examination to improve routine disease monitoring in RA.
Imaging Assessment of Rheumatoid Arthritis
Keywords: arthritis; rheumatoid arthritis; imaging; medical imaging; ultrasound; MRI; inflammation; bone erosion